2015
DOI: 10.1371/journal.pone.0140206
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Reproducibility of Twenty-Four-Hour Intraocular Pressure Curves in Untreated Patients with Primary Open-Angle Glaucoma and Ocular Hypertension

Abstract: PurposeTo assess the short-term day-to-day reproducibility of 24-hour intraocular pressure (IOP) curves in various respects in untreated primary open-angle glaucoma (POAG) and ocular hypertension (OHT) patients.Methods47 subjects with POAG and 34 subjects with OHT underwent IOP measurements every 2 hours in both eyes for consecutive 48 hours by a non-contact tonometer (NCT). IOP values at each time point were recorded. Mean IOP, peak IOP, time difference of peak IOP between two days and IOP fluctuation were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In the current study, the overall IOP of the OHTN group was increased, the mean IOP was higher, and the uctuation amplitude of the diurnal and nocturnal IOP (8.91 ± 3.07 mmHg) was signi cantly higher than that of the healthy control group (5.89 ± 0.86 mmHg). Xu et al [11] studied the repeatability of 24-h IOP monitoring in OHTN, and found that the two 24-h IOP uctuation values were 8.94 ± 3.03 mmHg and 9.06 ± 3.19 mmHg, which is similar to the results of the current study (8.91 ± 3.07 mmHg). At the same time, Xu et al reported that the peak IOP occurred at 6:00 h, and that the trough IOP was observed at 20:00 h, which is similar to the results of the current study.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, the overall IOP of the OHTN group was increased, the mean IOP was higher, and the uctuation amplitude of the diurnal and nocturnal IOP (8.91 ± 3.07 mmHg) was signi cantly higher than that of the healthy control group (5.89 ± 0.86 mmHg). Xu et al [11] studied the repeatability of 24-h IOP monitoring in OHTN, and found that the two 24-h IOP uctuation values were 8.94 ± 3.03 mmHg and 9.06 ± 3.19 mmHg, which is similar to the results of the current study (8.91 ± 3.07 mmHg). At the same time, Xu et al reported that the peak IOP occurred at 6:00 h, and that the trough IOP was observed at 20:00 h, which is similar to the results of the current study.…”
Section: Discussionsupporting
confidence: 89%
“…The IOP curves over 3 days may not be representative of the IOP pattern in the preceding years during which visual field and/or structural changes may have occurred. Some studies reported that both healthy subjects and glaucoma patients failed to show repeatable diurnal and circadian IOP pattern over a short period of time,17,34,35 whereas others found no significant differences in diurnal IOP fluctuation on 2 consecutive days 36,37. Second, blood pressure, which is associated with IOP, was not monitored 38,39.…”
Section: Discussionmentioning
confidence: 99%
“…As the “target pressure” is one main goal of glaucoma management, at least ideally, the best approach should consider reaching a circadian IOP profile, always within an IOP range that is deemed “safe” for each individual patient. In clinical practice this is rather hard to do, first because with the currently available tools for 24-h IOP assessment, this requires admission to the hospital and a considerable amount of effort and resources, and second because it has been observed that circadian profiles also tend to vary within the same patient [ 168 ]. Therefore, at least theoretically, in order to adopt the best possible management, more than one 24-h curve would be needed for each individual patient.…”
Section: -H Iop Evidence: How Can It Change Treatment Patterns and mentioning
confidence: 99%